Segmental myocardial viability by echocardiography at rest. (31st December 2023) - Halvorsrød, Marlene Iversen; Thorstensen, Anders; Kiss, Gabriel; Støylen, Asbjørn
Abstract: Background: Myocardial viability assessment adds value to the therapeutic decision-making of patients with ischemic heart disease. In this feasibility study, we investigated whether established echocardiographic measurements of post-systolic shortening (PSS), strain, strain rate and wall motion score (WMS) can discover viable myocardial segments. Our hypothesis is that non-viable myocardial segments are both akinetic and without PSS. Methods: The study population consisted of 26 examinations strictly selected by visible dysfunction. We assessed WMS, strain by speckle tracking and strain rate by tissue Doppler. The segments (16*26 = 416) were categorized into either normokinetic/hypokinetic or akinetic/dyskinetic and whether there was PSS. The reference method was the presence of scar with segmental percentage volume scar fraction >50%, detected by late gadolinium-enhanced cardiovascular magnetic resonance. Agreement with echocardiography was evaluated by Kappa coefficient. Results: WMS had Kappa coefficient 0.43 (sensitivity 99%, specificity 35%). Kappa coefficient of strain was 0.28 (sensitivity 98%, specificity 23%). By combining PSS in akinetic segments with WMS and strain, the Kappa coefficient was 0.06 and 0.08 respectively. Conclusion: Segmental viability was best shown by the presence of systolic function. Post-systolic shortening adds no value to the assessment of segmental myocardial viability.